Gun digest 2026 - Massaro, Philip P. (Gun Digest Books, an imprint of Caribou Media, 2025)
"For more than three-quarters of a century, the Gun Digest annual book has been the trusted source for up-to-date, detailed, and exciting information about firearms. Whether your interest is rifles, handguns or shotguns, Gun Digest informs and entertains. Shooters, collectors, hunters and anyone who has even the slightest interest in guns new and old will appreciate the variety of in-depth coverage that has made this iconic book so popular since the first edition in 1944. With features authored by a who's who of industry experts, including Craig Boddington, Ron Spomer, Wayne van Zwoll , Terry Wieland and dozens more, Gun Digest comprises more than 600 pages of information guaranteed to raise your Firearms I.Q." --Provided by Publisher.